Electron emission from glow-discharge cathode materials due to neon and argon ion bombardment - Szapiro, B., author; Rocca, Jorge J., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1989)
We have measured the electron yields of 7 glow-discharge cathode materials under bombardment by neon and argon ions with energies between 1 and 20 keV. The surfaces of the samples were conditioned by operating the materials as cold cathodes in a high-voltage glow discharge before the electron yield measurement. The materials studied are oxidized magnesium, oxidized aluminum, a molybdenum-aluminum oxide sintered composite, molybdenum, stainless steel, copper, and graphite. The dependence of electron yield on ion velocity was found to be approximately linear for all materials and gases, with the slopes being strongly material dependent. The corresponding glow-discharge current intensities were observed to have a supralinear dependence on the electron yield. The results are relevant to the design and modeling of cold cathode high-voltage glow discharges.